Acceleration harmonic estimation and suppression for hydraulic load simulator based on artificial bee colony with chaotic search strategy - Wan, Zhenshuai (Strojniški vestnik, 2024)
This paper presents a new hybrid algorithm based on artificial bee colony (ABC) and chaotic search strategy (CSS), known as ABC-CSS to solve the harmonic estimation problems in the case of time varying acceleration response signal. The ABC algorithm simulates the intelligent behavior of bees in nature to find high-quality nectar sources according to different divisions of labor. Aiming at the lack of diversity, poor global and local search ability, as well as slow convergence speed of ABC, an improved ABC based on CSS is proposed. The algorithm generates new neighborhood points by the transformation of chaotic and decision variables by carrier mapping, which provides a broader search space and better location of nectar sources for bees and recruited observation bees, and enhances the diversity of bee colonies. At the same time, the investigation of a local honey bee search better solves the algorithm problem of the local minimum and improves the convergence property of the ABC. Simulation and experimental studies are conducted to validate the superiority of the proposed ABC-CSS in harmonic estimation.prosthetics. Then, using the finite element and topology optimization methods, an optimized prosthetic leg model was developed according to the results of structural analyses performed by considering the loading conditions and boundary conditions during daily activities such as standing, walking, ascending and descending stairs. Finally, the prosthetic model was modified for a support-free additive manufacturing process and a socket and heel piece were added. The designed prosthetic leg model was fabricated using the additive manufacturing method with hard thermoplastic polyurethane (TPU) material. The final prosthetic leg design achieved a safety factor of 4.14 and a weight reduction of 50.37 % compared to the solid model. In addition, a 50 % reduction in material usage and a 32 % reduction in fabrication time were achieved through topology optimization and support-free design.
Keywords: artificial bee colony; chaos-decision variable; harmonic distortion; harmonic estimation; harmonic suppression